Collagen Biosynthesis in Osteoblast Cells Treated with Fish Collagen Peptides - Hema, G. S.; Shyni, K.; Prasad, M. Manu; Ninan, George; Mathew, Suseela (Fishery Technology, 2017)
Collagen is one of the most widely used biomaterials in tissue engineering and regenerative medicine. To investigate the effect of fish collagen peptides on the formation of collagen proteins by mature osteoblast cells, human osteoblast cells were treated with collagen peptide in both time and dose dependent manner. The stimulatory effect of collagen peptide was confirmed by western blot and immunocytochemistry analysis. The results clearly indicate that the presence of fish collagen peptides led to a dose dependent increase in collagen synthesis by osteoblast cells upto a concentration of 0.6 mg ml-1. However native collagen or collagen free protein hydrolysate failed to stimulate the production of collagen in osteoblast cells. The results show a stimulatory effect of fish collagen peptides on the collagen biosynthesis in osteoblast cells and suggest a possible mechanism for the regulation of collagen turnover in joint tissues.